A Convenient and Selective Palladium‐Catalyzed Aerobic Oxidation of Alcohols. Issue 47 (14th October 2013) - Gowrisankar, Saravanan; Neumann, Helfried; Gördes, Dirk; Thurow, Kerstin; Jiao, Haijun; Beller, Matthias
Abstract An efficient procedure for the oxidation of primary and secondary alcohols to aldehydes and ketones, respectively, with molecular oxygen under ambient conditions has been achieved. By applying catalytic amounts of Pd(OAc)2 in the presence of tertiary phosphine oxides (OPR3) as ligands, a variety of substrates are selectively oxidized without formation of ester byproducts. Spectroscopic investigations and DFT calculations suggest stabilization of the active palladium(II) catalyst by phosphine oxide ligands.